2017
DOI: 10.1002/pbc.26656
|View full text |Cite
|
Sign up to set email alerts
|

p16 Loss and E2F/cell cycle deregulation in infant posterior fossa ependymoma

Abstract: Background Posterior fossa (PF) ependymomas (EPNs) in infants less than 1 year of age (iEPN-PF) have a poorer clinical outcome than EPNs in older children. While radiation therapy is the standard of care for the latter, it is withheld in infants to avoid neurotoxicity to immature brain. It is unknown whether the adverse outcome in iEPN-PFs is due to treatment differences or aggressive biology. We examined this question using molecular profiling. Methods Six anaplastic iEPN-PFs were subjected to transcriptomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…In this study, we identified the upregulated miR-related signaling network in LCT-MF including ICOS-ICOSL signaling, PD1-PDL1 signaling, NF-κB signaling, E2F transcription, and molecular mechanisms of cancer pathways. Although these pathways have been consistent with previous studies in MF, other specific pathways of LCT-MF in this analysis, such as E2F transcription, have not been previously reported and are worthwhile to explore, as the interaction of malignant cells with E2F, for one, promotes a microenvironment suitable for tumor cell growth, survival, and aggressiveness [ 29 , 30 ]. Among the downregulated miRs, the miR with the most statistically significant log FC was the hsa-miR-708.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we identified the upregulated miR-related signaling network in LCT-MF including ICOS-ICOSL signaling, PD1-PDL1 signaling, NF-κB signaling, E2F transcription, and molecular mechanisms of cancer pathways. Although these pathways have been consistent with previous studies in MF, other specific pathways of LCT-MF in this analysis, such as E2F transcription, have not been previously reported and are worthwhile to explore, as the interaction of malignant cells with E2F, for one, promotes a microenvironment suitable for tumor cell growth, survival, and aggressiveness [ 29 , 30 ]. Among the downregulated miRs, the miR with the most statistically significant log FC was the hsa-miR-708.…”
Section: Discussionsupporting
confidence: 88%
“…32,33 Decreased expression of p16 in cell lines regulates the cell cycle via Rb and increases proliferation and oncogenic capacity. 34 Here, flow cytometry revealed that HQ chronic exposure or p16 lost promoted cell cycle from G 0 /G 1 to S and G 2 /M phases. Conversely, p16 overexpression inhibited the entry of HQ-TK6 cell from G 0 /G 1 to S and G 2 /M phases (p < .01; Figure 5A).…”
Section: P16 Is Involved In Acceleration Of Cell Cycle Progression In Hq-transformed Tk6 Cellsmentioning
confidence: 73%
“…CDK4 was likewise found overexpressed in EPN and associated with adverse outcomes [ 411 ]; accordingly, its inhibition restricted cell proliferation and reduced the expression of genes associated with the cell cycle and DNA repair ( CCNB1 , TOP2A , CDK2 , BRCA1 and RAD51 ), and induced morphological changes that culminated in cell death [ 412 ]. Considering EPN subgroups, De Almeida Magalhaes et al (2020) showed that CDK6 is overexpressed in ST-EPN-RELA tumors compared to other ST-EPN subgroups [ 413 ], even though others have suggested that the dysregulations of the p16-CDK4/6-pRB-E2F pathway might also compose the genetic background underlying the aggressive biology of posterior fossa EPN in infants less than 1 year old [ 414 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%